The inertia of certain Hermitian block matrices - Fonseca, C. M. da (1998)
We characterize sets of inertias of some partitioned Hermitian matrices by a system of inequalities involving the orders of the blocks, the inertias of the diagonal blocks, and the ranks of the nondiagonal blocks. The main result generalizes some well-known characterizations of Sá and Cain and others.